2018
DOI: 10.1007/s11606-017-4277-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Treatment of Hypertensive Urgency in the Outpatient Setting: A Systematic Review

Abstract: BackgroundHypertensive urgency (HU), defined as acute severe uncontrolled hypertension without end-organ damage, is a common condition. Despite its association with long-term morbidity and mortality, guidance regarding immediate management is sparse. Our objective was to summarize the evidence examining the effects of antihypertensive medications to treat.MethodsWe searched the PubMed, Cochrane Central Register of Controlled Trials (CENTRAL), Database of Abstracts of Reviews of Effects (DARE), Cochrane Databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
7

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
0
9
0
7
Order By: Relevance
“…This point requires further investigation, as we were unable to evaluate therapeutic modifications transferred at discharge with our local clinical data warehouse. Besides, OCA prescriptions are frequently given for patients admitted for reasons other than hypertension and initiated for a patient with no history of hypertension at the time of hospitalization . However, our subgroup analysis suggested that the probability of modification of a chronic treatment after OCA prescription during hospitalization was frequent.…”
Section: Resultsmentioning
confidence: 99%
“…This point requires further investigation, as we were unable to evaluate therapeutic modifications transferred at discharge with our local clinical data warehouse. Besides, OCA prescriptions are frequently given for patients admitted for reasons other than hypertension and initiated for a patient with no history of hypertension at the time of hospitalization . However, our subgroup analysis suggested that the probability of modification of a chronic treatment after OCA prescription during hospitalization was frequent.…”
Section: Resultsmentioning
confidence: 99%
“…с последующей коррекцией режима приема препаратов длительного действия [37][38][39]. В качестве такого перорального короткодействующего средства может быть использован каптоприл, эффективность и безопасность которого в данной ситуации хорошо изучена в том числе у пациентов пожилого возраста [40,41].…”
Section: Arterial Hypertension In Older Patientsunclassified
“…Каптоприл применялся в дозах 6,25-25 мг перорально или сублингвально, дозозависимый гипотензивный эффект отмечался в течение 0,17-12 ч с момента приема. Следует отметить, что каптоприл был единственным ингибитором ангиотензинпревращающего фермента, который изучался в ходе рандомизированных клинических исследований у пациентов с нГК [13].…”
Section: заключение совета экспертовunclassified